The Effect Of Product Quality And Service Quality On Customer Satisfaction And Customer Loyalty Case Study : At Manna Kampus Retail Store (Mirota Kampus 2) Simanjuntak In Yogyakarta - Ichsan Ramaditya; Albari Albari (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to explain the influence of product quality and service quality on customer satisfaction and customer loyalty, as well as the influence of customer satisfaction on customer loyalty. The population in this study consists of customers of Manna Kampus (Mirota Kampus 2) Simanjuntak in Yogyakarta, with a sample size of 100 customers. The sampling method used in this study is non-probability with a convenience sampling technique. Hypothesis testing in this study is conducted using the IBM SPSS 25 program. The results obtained show a positive influence of product quality and service quality on customer satisfaction. Both variables together with customer satisfaction can also positively influence customer loyalty.